The NLN Jeffries simulation theory 2026-02-16T09:24:03+03:00 DEBUG: VuFind\ILS\Driver\Folio: Token taken from global cache: eyJhbGciOiJIUzI1NiJ9.eyJzdWIiO... - Jeffries, Pamela R. (Wolters Kluwer, 2016)

(untitled)
"Developed through theoretical thinking and tested by nurse education researchers, the NLN Jeffries Simulation Theory helps to articulate phenomena that exist within clinical simulation. By establishing and communicating known relationships within these phenomena, this theory provides a strong foundation for research and education, and enables future discovery of best practices in simulation. Through rigorous research and literature review, and by incorporating the perspectives of nurses immersed in simulation activities, The NLN Jeffries Simulation Theory is an effective guide to implementation and further research." -- Publisher's website